2008
DOI: 10.1093/jee/101.3.759
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SPLAT with Spinosad and Methyl Eugenol or Cue-Lure for “Attract-and-Kill” of Oriental and Melon Fruit Flies (Diptera: Tephritidae) in Hawaii

Abstract: Specialized Pheromone and Lure Application Technology (SPLAT) methyl eugenol (ME) and cue-lure (C-L) "attract-and-kill" sprayable formulations containing spinosad were compared with other formulations under Hawaiian weather conditions against oriental fruit fly, Bactrocera dorsalis (Hendel), and melon fly, Bactrocera cucurbitae (Coquillett) (Diptera: Tephritidae), respectively. Field tests were conducted with three different dispensers (Min-U-Gel, Acti-Gel, and SPLAT) and two different insecticides (naled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Weathering of the new sprayable SPLAT-MAT ME and C-L lure and kill formulations with the reduced risk insecticide spinosad was also evaluated in Hawaii (Vargas et al 2008b) and California (Vargas et al 2010b). Research has focused on SPLAT ME and C-L as replacement for Min-UGel ME and C-L, both using the toxic naled insecticide (Vargas et al 2008b(Vargas et al , 2010b.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Weathering of the new sprayable SPLAT-MAT ME and C-L lure and kill formulations with the reduced risk insecticide spinosad was also evaluated in Hawaii (Vargas et al 2008b) and California (Vargas et al 2010b). Research has focused on SPLAT ME and C-L as replacement for Min-UGel ME and C-L, both using the toxic naled insecticide (Vargas et al 2008b(Vargas et al , 2010b.…”
Section: Discussionmentioning
confidence: 99%
“…Research has focused on SPLAT ME and C-L as replacement for Min-UGel ME and C-L, both using the toxic naled insecticide (Vargas et al 2008b(Vargas et al , 2010b. In trials conducted in California, chemical analyses of the weathered SPLAT formulation suggested a more rapid loss of ME than C-L from different dispensers (R. I.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fipronil-based Amulet C-L stations (Vargas et al 2005) were recently registered for male annihilation technique. A sprayable SPLAT-ME is currently undergoing registration with the United States Environmental Protection Agency (Mau et al 2007, Vargas et al 2008b). The development of IPM approaches that include a solid lure/toxicant wafer trap for monitoring would have important applications to detection and monitoring of fruit ßies not only in Hawaii but also throughout the south and western PaciÞc, Australia, and tropical Asia where Bactrocera are serious economic pests.…”
Section: Discussionmentioning
confidence: 99%